Geroprotective applications of oleuropein and hydroxytyrosol through the hallmarks of ageing - Anna Calabrò; Anna Aiello; Paula Silva; Calogero Caruso; Giuseppina Candore; Giulia Accardi (GeroScience, 2025)
Geroprotectors are compounds that target the underlying mechanisms of ageing to delay the onset of age-related diseases and extend both lifespan and health span. As ageing is driven by the accumulation of cellular damage, DNA instability, epigenetic changes, mitochondrial dysfunction, and chronic inflammation, the concept of geroprotection focuses on compounds that can mitigate these processes. Oleuropein (OLE) and its derivative hydroxytyrosol (HT), both phenolic molecules derived from Olea europaea (olive tree), have gained significant attention as potential geroprotectors due to their potent antioxidant and anti-inflammatory properties. These phytochemicals, central to the Mediterranean diet, activate key molecular pathways such as nuclear factor erythroid 2-related factor 2, reducing oxidative stress and modulating inflammatory responses. Through these mechanisms, OLE and HT help counteract inflammageing, a critical factor in age-related dysfunction. This review highlights the role of OLE and HT as geroprotective agents, emphasising their ability to target the hallmarks of ageing and their potential to improve health span by slowing the progression of age-related conditions. With proven efficacy in various biological models, these compounds represent promising tools in the ongoing search for strategies to enhance the quality of life in ageing populations.

Deciphering the evolvement of microbial communities from hydrothermal vent sediments in a global change perspective - Carmen Rizzo; Erika Arcadi; Rosario Calogero; Alessandro Ciro Rappazzo; Gabriella Caruso; Giovanna Maimone; Angelina Lo Giudice; Teresa Romeo; Franco Andaloro (Environmental Research, 2024)

Age-associated changes in circulatory fatty acids: new insights on adults and long-lived individuals - Sawan Ali; Anna Aiello; Tiziana Zotti; Giulia Accardi; Gaetano Cardinale; Pasquale Vito; Anna Calabrò; Mattia Emanuela Ligotti; Mariano Intrieri; Graziamaria Corbi; Calogero Caruso; Giuseppina Candore; et al. (GeroScience, 2023)

A new standardized phytoextract from red orange and lemon wastes (red orange and lemon extract) reduces basophil degranulation and activation - Massimo Caruso; Simona Fabroni; Rosalia Emma; Gabriele Ballistreri; Margherita Amenta; Walter Currenti; Calogero Rinzivillo; Paolo Rapisarda (Natural Product Research, 2021)

Erratum to: Modulation of Nrf2/ARE Pathway by Food Polyphenols: A Nutritional Neuroprotective Strategy for Cognitive and Neurodegenerative Disorders - Giovanni Scapagnini; Sonya Vasto; Nader G. Abraham; Calogero Caruso; Davide Zella; Fabio Galvano (Molecular Neurobiology, 2011)

Modulation of Nrf2/ARE Pathway by Food Polyphenols: A Nutritional Neuroprotective Strategy for Cognitive and Neurodegenerative Disorders - Giovanni Scapagnini; Vasto Sonya; Abraham G. Nader; Caruso Calogero; Davide Zella; Galvano Fabio (Molecular Neurobiology, 2011)

Palermo-2010 conference on biogerontology - Sonya Vasto; Giuseppina Candore; Giuseppina Colonna-Romano; Calogero Caruso (Biogerontology, 2011)

Analysis of polymorphisms Leiden Factor V G1691A and prothrombin G20210A as risk factors for acute myocardial infarction - Giusi Irma Forte; Loredana Vaccarino; Marisa Palmeri; Angelo Branzi; Claudio M. Caldarera; Letizia Scola; Calogero Caruso; Federico Licastro; Domenico Lio (Biogerontology, 2011)

B cell immunosenescence: different features of naive and memory B cells in elderly - Silvio Buffa; Matteo Bulati; Mariavaleria Pellicanò; Deborah K. Dunn-Walters; Yu-Chang Wu; Giuseppina Candore; Salvatore Vitello; Calogero Caruso; Giuseppina Colonna-Romano (Biogerontology, 2011)

Blood group does not appear to affect longevity a pilot study in centenarians from Western Sicily - Sonya Vasto; Calogero Caruso; Laura Castiglia; Giovanni Duro; Roberto Monastero; Claudia Rizzo (Biogerontology, 2011)

Role of prothrombotic polymorphisms in successful or unsuccessful aging - Loredana Vaccarino; Giusi Irma Forte; Marisa Palmeri; Gabriella Misiano; Elisa Porcellini; Martina Chiappelli; Letizia Scola; Calogero Caruso; Federico Licastro; Domenico Lio (Biogerontology, 2011)

Inflammation, genetic background and longevity - Giuseppina Candore; Calogero Caruso; Giuseppina Colonna-Romano (Biogerontology, 2010)

Alpha1-antitrypsin heterozygosity plays a positive role in attainment of longevity - Florinda Listì; Giuseppina Candore; Maria Paola Grimaldi; Domenico Lio; Giuseppina Colonna-Romano; Valentina Orlando; Marco Caruso; Enrico Hoffmann; Giuseppe Paolisso; Claudio Franceschi; Calogero Caruso (Biogerontology, 2007)

Inflammation, genes and zinc in ageing and age-related diseases - Sonya Vasto; Eugenio Mocchegiani; Giuseppina Candore; Florinda Listì; Giuseppina Colonna-Romano; Domenico Lio; Marco Malavolta; Robertina Giacconi; Catia Cipriano; Calogero Caruso (Biogerontology, 2006)

Involvement of −308 TNF-α and 1267 Hsp70-2 polymorphisms and zinc status in the susceptibility of coronary artery disease (CAD) in old patients - Robertina Giacconi; Catia Cipriano; Elisa Muti; Laura Costarelli; Marco Malavolta; Calogero Caruso; Domenico Lio; Eugenio Mocchegiani (Biogerontology, 2006)

Study of the Association with −330T/G IL-2 in a Population of Centenarians from Centre and South Italy - Letizia Scola; Giuseppina Candore; Giuseppina Colonna-Romano; Antonio Crivello; Giusi I. Forte; Giuseppe Paolisso; Claudio Franceschi; Domenico Lio; Calogero Caruso (Biogerontology, 2005)

Effects of isokinetic, isotonic and isometric submaximal exercise on heart rate and blood pressure - Ferdinando Iellamo; J. M. Legramante; Gianfranco Raimondi; Filippo Castrucci; C. Damiani; Calogero Foti; Giuseppe Peruzzi; Ignazio Caruso (European Journal of Applied Physiology, 1997)